2014
DOI: 10.13080/z-a.2014.101.026
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation technology influences the occurrence of potato early blight (Alternaria solani) in an organic farming system

Abstract: Nowadays, organically produced products have become more popular than ever and interest in them is still growing fast. The early blight causal pathogen Alternaria solani has not been considered a great threat to potato in northern climate conditions in the past and has not been routinely sprayed against. During our study early blight was evaluated in 2010 and 2011 on the plants of a potato cultivar 'Reet' in an organic farming experiment. In our study, both growing seasons were very favourable for early blight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The products tested in the cited study (Bioilsa Fertil NC, EM Farma Plus, UGmax) delayed the onset of disease, prolonged the growing season (in particular when disease severity was low) and protected crops. Runno-Paurson et al (2014) reported higher tuber yields in treatments where intercropping and manure fertilizers were used. Potato leaves were more severely infected with Alternaria spp.…”
Section: Assessment Of Potato Tuber Yield By Linear Regression Analysismentioning
confidence: 95%
“…The products tested in the cited study (Bioilsa Fertil NC, EM Farma Plus, UGmax) delayed the onset of disease, prolonged the growing season (in particular when disease severity was low) and protected crops. Runno-Paurson et al (2014) reported higher tuber yields in treatments where intercropping and manure fertilizers were used. Potato leaves were more severely infected with Alternaria spp.…”
Section: Assessment Of Potato Tuber Yield By Linear Regression Analysismentioning
confidence: 95%
“…Long-term organic crop rotation systems can have even more nitrogen in the soil than the conventional farming systems [34]. Runno-Paurson et al [35] also reported that the addition of manure will increase the early blight pressure, but it does not affect the yield.…”
Section: Resultsmentioning
confidence: 99%
“…Different cruciferous crops like winter oilseed rape, white mustard (Sinapis alba L.) and oilseed radish (Raphanus sativus (L.)) have been used quite successfully as green manure and cover crops to supress soilborne pathogens and reduce foliar disease progression (Larkin et al, 2010;Larkin, 2017;Olanya et al, 2014;Runno-Paurson et al, 2014, 2019. Use of cover crops could be a promising alternative disease control strategy for environmentally friendly producers.…”
Section: Introductionmentioning
confidence: 99%